Ángel Crespo en Lisboa, el poeta y la ciudad - MUÑOZ CARROBLES, Diego (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2009)
In this paper we are going to analyze and describe Lisbon, a book written by the poet Angel Crespo, like a personal travel guide. First he approaches us tu the mythic origins of the city and he describes briefly the city’s main historical facts. After that he shows us his favourite places in the city, while he designs several “walks” and comments the most interesting points of each one.